The Effectiveness of Nutrition Education by Health Workers on Improving Knowledge and Attitudes of Pregnant Women in Stunting Prevention - Sitorus, Rotua Sumihar (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Stunting remains a major public health issue in Indonesia, with long-term effects on children’s development. Nutrition education for pregnant women is a crucial early intervention strategy for stunting prevention. Objective: This study aimed to analyze the effectiveness of nutrition education by health workers in improving pregnant women’s knowledge and attitudes toward stunting prevention. Research Methods: A quantitative study with a cross-sectional approach was conducted among 96 pregnant women in the Lubuk Pakam Health Center area. Data were collected through questionnaires and analyzed using chi-square tests and multivariate logistic regression. Results: Most participants received good nutritional education (60.42%), had high knowledge (54.17%), and showed positive attitudes (64.58%). Good nutrition education significantly increased the odds of having high knowledge (OR = 2.90; p = 0.004) and positive attitudes (OR = 3.29; p = 0.002). Conclusion: Nutrition education is effective in improving knowledge and attitudes of pregnant women regarding stunting prevention. Structured and accessible nutrition education should be strengthened in antenatal care services.